2020
DOI: 10.1177/0003134820973364
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Activity Trackers With vs. Without Alarms to Increase Postoperative Ambulation: A Randomized Control Trial

Abstract: Early ambulation is a key component to postoperative recovery; however, measuring steps taken is often inconsistent and nonstandardized. This study aimed to determine whether an activity tracker with alarms would increase postoperative ambulation in patients after elective colorectal procedures. Forty-eight patients were randomly assigned to either trackers with 5 daily alarms or activity trackers alone. Over 223 total patient days, the trackers recorded a complete data set for 216 patient days (96.9%). Increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 16 publications
(19 reference statements)
0
22
0
Order By: Relevance
“…All studies used accelerometers during the acute inpatient period (per our inclusion criteria). Of the 15 studies, 12 (80%) applied the device within a day after surgery (n=7, 58%, studies on the day of surgery [ 30 - 32 , 35 , 36 , 38 , 39 ] and n=5, 42%, studies on postoperative day 1 or within 24 hours after surgery [ 27 , 29 , 33 , 37 , 40 ]). Of the 15 studies, 2 (13%) started the device wear after patients were transferred to the floor from the intensive care unit, which occurred on postoperative day 2 or 3 on average [ 28 , 41 ], and 1 (7%) did not report the timing of initiation [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies used accelerometers during the acute inpatient period (per our inclusion criteria). Of the 15 studies, 12 (80%) applied the device within a day after surgery (n=7, 58%, studies on the day of surgery [ 30 - 32 , 35 , 36 , 38 , 39 ] and n=5, 42%, studies on postoperative day 1 or within 24 hours after surgery [ 27 , 29 , 33 , 37 , 40 ]). Of the 15 studies, 2 (13%) started the device wear after patients were transferred to the floor from the intensive care unit, which occurred on postoperative day 2 or 3 on average [ 28 , 41 ], and 1 (7%) did not report the timing of initiation [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mean in-hospital wear duration was 5.2 (SD 2.0; range 3-10) days. Most of the studies (11/15, 73%) described continuous 24-hour device wear with or without brief interruptions for battery charging or patient showering [ 27 - 30 , 32 - 34 , 36 , 38 , 39 , 41 ], whereas others implied continuous measurement but did not explicitly describe it [ 31 , 35 , 37 , 40 ]. Of the 15 studies, 3 (20%) obtained preoperative baseline data, ranging from 2 to 30 days before surgery [ 31 , 35 , 40 ], and 1 (7%) followed patients after discharge until postoperative day 30 [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, a non-randomized trial showed a lower risk of pneumonia and shorter duration of hospital stay in a self-selected group of patients 93 . Feedback from wearable devices had mixed effects; some studies reported increased activity 74 , 94 , whereas others reported no effect 63 , 95 .…”
Section: Resultsmentioning
confidence: 99%